Being Tough Versus Tender: The Impact of Country‐Level and Individual Masculinity Orientations as Moderators of the Relationship Between Job Insecurity and Job Attitudes. Issue 3 (15th April 2019) - Debus, Maike E.; Kleinmann, Martin; König, Cornelius J.; Winkler, Silvan
Abstract : Having a job constitutes one of the most potent means of attaining 'masculine' goals such as status, success, and material rewards. In the present research, we examine whether masculinity, both as a country‐level value and an individual orientation, moderates the relationship between job insecurity and job attitudes. In Study 1, we draw on cross‐cultural data of 20, 988 employees from 17 countries. We find that job insecure individuals from countries with higher masculinity values show stronger decrements in job satisfaction (but not commitment). Shedding light on the underlying mechanism, we show that the moderating effect of masculinity is transmitted through two social job characteristics, perceived supervisor interpersonal justice and coworker support. We then constructively replicate the moderating effect of masculinity in Study 2. In a one‐country sample of 319 employees, individual masculinity orientations likewise strengthen the negative relationship between job insecurity and job satisfaction. Our research highlights that country‐level and individual masculinity orientations yield comparable effects in the job insecurity appraisal process, and provides insight into how cultural values can be enacted at the individual level.